Location and characterization of the Sancti Spiritus Fort from geophysical investigations - Bonomo, Nestor Eduardo (2012)
A geophysical investigation was carried out to locate and characterize the remains of the Sancti Spiritus Fort, the first European settlement in the South Cone of America (1527-1529). In an initial stage, we used three complementary methods, ground penetrating radar, multifrequency electromagnetic induction and dipole-dipole electric profiling, to increase the possibility of detecting the structures of the Fort whose physical properties were expected to be similar to those of the surrounding soil, as they were constructed with raw earth probably extracted from it. From different views of the data, a number of electromagnetic signals apparently related to these structures were identified. Test excavations confirmed these hypotheses and showed that the structures were poorly preserved. Furthermore, they were almost indistinguishable through direct inspection of the excavated sections of soil, and very difficult to track. Therefore, in a second stage of geophysical studies, we acquired high-density grids of GPR data at relevant areas, looking for more detailed information about the structures. The results of these studies allowed to determine with precision their continuity through the site and also to interpret a number of areas which had remained unclear from the first survey. Extensive archaeological excavations were designed from the geophysical maps and carried out. From them, the geophysical interpretations were fully confirmed, and the presence of structural elements of previous and later native settlements was established. © 2012 Elsevier B.V.